Industrial metabolism of iron and carbon with substance flow analysis in iron and steel industry - Junwen Chen; Qing Sun (PLoS ONE, 2025)
Iron and carbon are inextricably linked from the source to the destination in iron and steel system. With the shortage of iron ore and severe pollution caused by emissions, it is pressing to improve resource efficiency and reduce pollution. To comprehensively evaluate resource efficiency and understand the metabolic processes of iron and carbon, SFA (Substance flow analysis) was considered as an effective assessment method to assess the resource efficiency. In this paper, a widespread SFA model is proposed, and four evaluation indicators are proposed to appraise the metabolic processes of iron and carbon. According to the data of a state-owned and large-scaled steel enterprise in China, metabolic network of iron and carbon are established. The results of this study showed that the resource utilization efficiency of iron is 86.77%, and that of carbon is 0.33%. Focus is given onto the metabolic processes of iron and carbon in BOF and EAF, as well as the iron-carbon metabolism nexus. When considering the material and energy metabolism of the upstream process, the molten iron ratio is inversely proportional to the electricity consumption intensity and directly proportional to the carbon emission intensity. The average emission intensity will decrease 83.00 kg CO2/t molten steel if the molten iron ratio decreases 0.05 in EAF, while electricity consumption intensity increases 32.00 kwh/t molten steel.